2008
DOI: 10.1038/cdd.2008.120
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and cell death in model organisms

Abstract: Autophagy evolved in unicellular eukaryotes as a means for surviving nutrient stress. During the course of evolution, as multicellular organisms developed specialized cell types and complex intracellular signalling networks, autophagy has been summoned to serve additional cellular functions. Numerous recent studies indicate that apart from its pro-survival role under nutrient limitation, autophagy also participates in cell death. However, the precise role of this catabolic process in dying cells is not fully u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
197
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(208 citation statements)
references
References 87 publications
2
197
0
7
Order By: Relevance
“…We hypothesized that the numerous vesicles might originate from induction of autophagy because many cell types exhibit massive vacuolization during autophagy-associated cell death [27,28]. In agreement with the massive vacuolization on PMA stimulation, which was observed by live cell imaging ( Figure 1; Supplementary information, Video S1), transmission electron microscopic analysis of neutrophils revealed the presence of vesicles with double membranes ( Figure 3A).…”
Section: Pma-induced Vacuolization Involves Autophagy and Occurs Indesupporting
confidence: 60%
See 1 more Smart Citation
“…We hypothesized that the numerous vesicles might originate from induction of autophagy because many cell types exhibit massive vacuolization during autophagy-associated cell death [27,28]. In agreement with the massive vacuolization on PMA stimulation, which was observed by live cell imaging ( Figure 1; Supplementary information, Video S1), transmission electron microscopic analysis of neutrophils revealed the presence of vesicles with double membranes ( Figure 3A).…”
Section: Pma-induced Vacuolization Involves Autophagy and Occurs Indesupporting
confidence: 60%
“…Bacterial challenge is known to induce Nox2 activation [27], but it can also induce autophagy [35,36]. It was recently shown that engagement of Toll-like receptor and Fc receptor signaling during phagocytosis induces autophagy in primary neutrophils [36].…”
Section: Wwwcell-researchcom | Cell Research Quinten Remijsen Et Almentioning
confidence: 99%
“…Autophagy is also triggered as an adaptive response to a broad range of other extracellular or intracellular stressors such as hypoxia, heat, reactive oxygen species (ROS) and accumulation of damaged cytoplasmic components (Levine and Klionsky, 2004). Suppression of autophagy by knockout or knockdown of essential autophagy genes triggers apoptosis or necrosis in cells that would otherwise survive under stress conditions (reviewed in Kourtis and Tavernarakis, 2009;Mathew et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive autophagy induced by extreme conditions, such as toxins and necrosis-triggering insults, might cause uncontrollable degradation or sequestration of cells contents into autophagosomes resulting in undesirable cell death if not properly regulated (reviewed in Kourtis and Tavernarakis, 2009;Yang and Klionsky, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the first issue of 2009, Cell Death and Differentiation has already published nine reviews on the topic of autophagy in aging, disease and death. [1][2][3][4][5][6][7][8][9] These are now followed by another six papers covering more specific aspects of the complex regulation of this process and its crosstalk with apoptosis and other essential cellular functions, such as energy production, vesicular traffic and cellular immunity. [10][11][12][13][14][15] Three reviews focus on the molecular mechanisms regulating the induction, formation and maturation of the autophagosome vesicles.…”
mentioning
confidence: 99%